Simulasi Antrian Pelanggan Mixue Krakatau Dengan Algoritma First In First Out (FIFO) - Butar-Butar, Pade Armadan Butar-Butar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Queuing problems, the problem faced during the queuing process for taking the queue receipt to get ice cream at Mixue Krakatau is the irregularity in calling the queue serial number which causes a rush when queuing for ice cream which can make the queue atmosphere disorderly and disorganized. . Queuing is a process related to the arrival of consumers to a service facility. If they cannot be served, they have to wait in a queue until they are served and finally leave the facility after being served. One solution to handle the problem of queuing services and ordering queue receipts is to increase the number of machines that handle ice cream and drinks in Mixue Kakatau so that queues run regularly, it should be implemented in a way or approach that is expected to solve the problem of the ordering process and customer views, namely a tiered queuing system where queuing is often used to achieve discipline with the First In First Out (FIFO) method, which is a method for solving queuing problems that can be applied in a way that the customer who first arrives or enters is assumed to be the first to leave. Research results from customer queue simulations using the FIFO (First In First Out) method. It was obtained that the final results of testing the Krakatau Mixue customer ordering queue system gave the smallest value for AWP (Avarage Waiting Process) with an average queue processing time of 10.7 minutes. Implementation using one of the solutions provided by the author gives the final result of the smallest value of AWT (Avarage Waiting Time) with an average service waiting time of 12.9 minutes. AWP (Avarage Waiting Process) average queue processing time is 10.7 minutes. The smallest value of AWT (Avarage Waiting Time) is the average service waiting time of 11.3 minutes.